2016
DOI: 10.1186/s13052-016-0304-1
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with active commuting to school by bicycle from Bogotá, Colombia: The FUPRECOL study

Abstract: BackgroundActive commuting to school (ACS) can contribute to daily physical activity (PA) levels in children and adolescents. The aim of the study was to analyze the characteristics of active commuting to and from school by bicycle and to identify the factors associated with the use of bicycles for active commuting to school based in a sample of schoolchildren in Bogotá, Colombia.MethodsA cross-sectional study was conducted in 8,057 children and adolescents. A self-reported questionnaire was used to measure fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
8
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 49 publications
2
8
0
1
Order By: Relevance
“…We chose the age range 12 to 15 as a study conducted in Finland between 1980 and 2007 found that the rate of active commuting to school (ACTS), including both walking and cycling, decreased sharply between the ages of 12 and 15 [ 14 ], suggesting that this age range might be a high-risk population. Similar findings were reported for cycling to school in a study conducted in Colombia where more children up to 12 years cycled to school compared with adolescents aged 13 and older [ 15 ]. However, we reported very high rates of cycling to school among 12- to 15-year olds in our recent study [ 12 ], suggesting that the contexts in which cycling to school occurs also vary by countries.…”
Section: Introductionsupporting
confidence: 86%
“…We chose the age range 12 to 15 as a study conducted in Finland between 1980 and 2007 found that the rate of active commuting to school (ACTS), including both walking and cycling, decreased sharply between the ages of 12 and 15 [ 14 ], suggesting that this age range might be a high-risk population. Similar findings were reported for cycling to school in a study conducted in Colombia where more children up to 12 years cycled to school compared with adolescents aged 13 and older [ 15 ]. However, we reported very high rates of cycling to school among 12- to 15-year olds in our recent study [ 12 ], suggesting that the contexts in which cycling to school occurs also vary by countries.…”
Section: Introductionsupporting
confidence: 86%
“…A higher level of educational achievement (university or postgraduate) was correlated with a greater probability of the child actively commuting to school by bicycle. 6 The primary limitations of this study are inherent to its crosssectional nature and the type of sample used. It would be important to increase the population sample studied by including different age groups, or by expanding the survey to private schools.…”
Section: Discussionmentioning
confidence: 99%
“…4 In youths, several factors have been described as more or less influential determinants regarding the decision to commute actively, including socioeconomic status, characteristics of the natural environment, parental educational level, social support for active commuting, distance between school and home, and the perceptions of parents and children regarding neighborhood characteristics. 5,6 Despite the importance of AST as a strategy to promote physical activity in achieving the international physical activity guidelines of the World Health Organisation and the high rates of physical inactivity (≈70%) and sedentary lifestyles among students in Bogotá, 7,8 to date few studies have analyzed correlates and healthrelated associations in this population. 6,9 Thus, the aim of the present study was to analyze the association between cycling to and from school and adiposity, physical fitness, and cardiometabolic risk factors in a sample of Colombian children and adolescents.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, a high proportion of the studies included in this review were conducted in Spain, where rates of cycling to and from school are uncommon, and students usually prefer walking to and from school [60]. Moreover, although commuting distance to and from school is the most common factor that can determine the decision to actively commute [26,61,62], none of the studies in this review included the distance of the commute to and from school as a covariate in their analyses. Along these lines, two studies [25,50] in this review showed that a longer duration (an indirect indicator of distance) of ACS may have had a positive influence on academic achievement and cognitive performance in children and adolescents.…”
Section: Discussionmentioning
confidence: 99%